Controversy of the Qibla direction determination in Kendari city, Indonesia - MUHALLING, R.; HASBI, M.; NAJMAH, ST.; ANSELLA, S. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Problems arise in Kendari City because a determination of the Qibla on most mosques was not based on the accuracy of geographical direction but rather by consensus and belief. So, it was rather to the issue of aesthetic adaptation related to spatial planning and shaf and the problem of waqf rhetoric. In the process of adaptation, there are those who immediately make adjustments to safekeeping arrangements, and some others delay on the grounds that they must be discussed because they relate to worship more completely. RESUMEN Los problemas surgen en la ciudad de Kendari porque la determinación de la Qibla en la mayoría de las mezquitas no se basó en la precisión de la dirección geográfica, sino en el consenso y la creencia. Entonces, se trataba más bien de la cuestión de la adaptación estética relacionada con la planificación espacial y el shaf, y el problema de la retórica del waqf. En el proceso de adaptación, hay quienes inmediatamente hacen ajustes a los arreglos de custodia y algunos otros se demoran con el argumento de que deben discutirse porque se relacionan con el culto más completo.